2019
DOI: 10.4269/ajtmh.18-0103
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Renal Mucormycosis in Immunocompetent Hosts: Clinical Spectrum and Management Approach

Abstract: Isolated renal mucormycosis in immunocompetent hosts is a rare entity. We present the largest case series of isolated renal mucormycosis in immunocompetent hosts. Retrospective data of isolated renal mucormycosis from March 2012 to June 2017 was reviewed. Fifteen patients of isolated renal mucormycosis were identified. Contrastenhanced computed tomography scan showed enlarged globular kidneys with decreased or patchy enhancement, perinephric stranding and thickened Gerota's fascia in all patients. Ten patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…Contaminated intramuscular injections and surgery, adhesive tapes, and endobronchial tubes were sources of infection in nosocomial mucormycosis [ 16 , 22 , 36 , 37 ]. Isolated renal mucormycosis in an immunocompetent host is an emerging entity in India; the pathogenesis of the disease is still not known [ 38 , 39 ].…”
Section: Underlying Disease and Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Contaminated intramuscular injections and surgery, adhesive tapes, and endobronchial tubes were sources of infection in nosocomial mucormycosis [ 16 , 22 , 36 , 37 ]. Isolated renal mucormycosis in an immunocompetent host is an emerging entity in India; the pathogenesis of the disease is still not known [ 38 , 39 ].…”
Section: Underlying Disease and Risk Factorsmentioning
confidence: 99%
“…Prakash et al reported haemodialysis and CKD as significant risk factors in renal mucormycosis patients [ 5 ]. Isolated renal mucormycosis can affect unilateral or bilateral kidneys [ 38 , 39 ]. Patients present with fever, flank pain, haematuria or dysuria, acute kidney injury, and white flakes in urine [ 38 , 39 ].…”
Section: Clinical Forms Of Mucormycosismentioning
confidence: 99%
See 2 more Smart Citations
“…1 These infections are opportunistic and are mainly noted in individuals with compromised immunity although of late few cases in immunocompetent individuals have also been reported. [2][3][4]…”
Section: Introductionmentioning
confidence: 99%